2017
DOI: 10.1371/journal.pone.0186355
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gastrointestinal bacterial population for the production of holocellulose enzymes for biomass deconstruction

Abstract: The gastrointestinal (GI) habitat of ruminant and non-ruminant animals sustains a vast ensemble of microbes that are capable of utilizing lignocellulosic plant biomass. In this study, an indigenous swine (Zovawk) and a domesticated goat (Black Bengal) were investigated to isolate bacteria having plant biomass degrading enzymes. After screening and enzymatic quantification of eighty-one obtained bacterial isolates, Serratia rubidaea strain DBT4 and Aneurinibacillus aneurinilyticus strain DBT87 were revealed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 51 publications
4
13
0
Order By: Relevance
“…The maximum xylanase production (884.8 mU/mL) was observed at 7 days ( Figure 3 ), this finding had a similar trend to results on different xylanolytic gut bacteria [57] . On the other hand, the anaerobic bacterial community in this study produced more xylanase than the aerobic fungi [58] and anaerobic rumen fungi of the camel gut [21] .…”
Section: Discussionsupporting
confidence: 81%
“…The maximum xylanase production (884.8 mU/mL) was observed at 7 days ( Figure 3 ), this finding had a similar trend to results on different xylanolytic gut bacteria [57] . On the other hand, the anaerobic bacterial community in this study produced more xylanase than the aerobic fungi [58] and anaerobic rumen fungi of the camel gut [21] .…”
Section: Discussionsupporting
confidence: 81%
“…DBT14 require 120 h and 48 h incubation time respectively for maximum cellulase (FPase ~ 0.5 U/mL) activity. An optimum pH 7 for optimized growth as well as enzyme activity was reported in previous studies also ( Asem et al, 2017 , Raj et al, 2006 ). The growth characteristics revealed that the lag phase was observed up to 4 h only, logarithmic growth was observed from 8 h to 36 h of incubation followed by a decline in growth after 40 hr.…”
Section: Discussionsupporting
confidence: 74%
“…These microorganisms synthesize lignocellulolytic enzymes active under different pH and temperature conditions (Gao et al 2018; Gastelum-Arellanez et al 2014; Zhang et al 2017). The genus Aneurinibacillus is part of the ruminal microbiota able to synthesize enzymes that work on lignocellulose (Asem et al 2017). In contrast, Microbacterium species contain few genes encoding for lignocellulolytic enzymes; however, possess a great metabolic potential to degrade arabinoxylans (Yeager et al 2017).…”
Section: Discussionmentioning
confidence: 99%